Nanoemulsified Corn Oil in Lactating Barki Nutrition: Effect on Intake, Nutrient Digestibility, Rumen Fermentation Characteristics, and Microbial Population - Min Gao; Rong-Qing Li; Mostafa S. A. Khattab; Ahmed M. Abd El Tawab; Yong-Bin Liu; Mohamed El-Sherbiny (Animals)
Nanoemulsified corn oil was tested on twenty-one multiparous lactating Barki ewes (mean ± SD: 3 ± 0.4 parity, 44.3 ± 1.9 kg body weight, 30 ± 2.7 months of age, and 402 ± 23 g/d of prior milk production) randomly allocated to the following treatments (n = 7 ewes/group): Control—a basal diet consisting of 50% concentrate mixtures and 50% berseem clover; CO—the Control diet + 3% of corn oil; NCO—the Control diet + 3% of nanoemulsified corn oil. A completely randomized design of 25 days of adaptation and 5 days of sampling was employed with seven ewes per treatment. Despite feeding oil according to the recommended values, CO decreased the dry matter intake by 8.3% and 6.7% compared to the Control and NCO, respectively. The negative impact of CO extended to reducing the concentrations of ammonia and total volatile fatty acids in the rumen. On the other hand, NCO had less effect on the biohydrogenation intermediates profile compared to CO; noticeably, higher proportions of unsaturated fatty acid (UFA) were associated with NCO; these results were also supported by an increase in the rumen microbial population with NCO compared to CO, especially the biohydrogenation bacteria, which showed higher abundance with NCO despite the low presence of biohydrogenation intermediates. In conclusion, the NCO demonstrated the ability to decrease the transformation of unsaturated fatty acids into saturated fatty acids in the biohydrogenation environment. This effect was not associated with decreased dry matter intake, changes in nutrient digestibility, or alterations in fermentation patterns.